2014
DOI: 10.1007/s12016-014-8461-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Recommendations for the Use of Islet Cell Autoantibodies to Distinguish Autoimmune and Non-Autoimmune Gestational Diabetes

Abstract: Gestational diabetes mellitus (GDM) is defined as carbohydrate intolerance that begins or is first recognized during pregnancy. The prevalence of GDM is highly variable, depending on the population studied, and reflects the underlying pattern of diabetes in the population. GDM manifests by the second half of pregnancy and disappears following delivery in most cases, but is associated with the risk of subsequent diabetes development. Normal pregnancy induces carbohydrate intolerance to favor the availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 124 publications
1
18
0
Order By: Relevance
“…[5][6][7] This differs from other types of diabetes such as monogenic or type 1 diabetes which have genetic and/or autoimmune origins. 8,9 Both pre-existing T2D and GDM are diagnosed through measurement of glycemia, and they are generally distinguished from each other by the timing of the diagnosis in reference to the gestational period, as GDM develops after the 20 th gestational week and usually resolves within six weeks post-partum. 10 Typically, GDM is diagnosed with an oral glucose tolerance test (OGTT) undergone between 24 and 28 weeks of gestation and during which the fasting pregnant woman drinks a solution containing 75g or 100 g of glucose.…”
Section: Résumémentioning
confidence: 99%
“…[5][6][7] This differs from other types of diabetes such as monogenic or type 1 diabetes which have genetic and/or autoimmune origins. 8,9 Both pre-existing T2D and GDM are diagnosed through measurement of glycemia, and they are generally distinguished from each other by the timing of the diagnosis in reference to the gestational period, as GDM develops after the 20 th gestational week and usually resolves within six weeks post-partum. 10 Typically, GDM is diagnosed with an oral glucose tolerance test (OGTT) undergone between 24 and 28 weeks of gestation and during which the fasting pregnant woman drinks a solution containing 75g or 100 g of glucose.…”
Section: Résumémentioning
confidence: 99%
“…In most cases the body is able to compensate for this with increased insulin secretion and most cases resolves with delivery. [ 2 , 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this latter risk seems especially great when GDM is associated with type 1 diabetes autoantibodies (5,6). Nilsson et al (6) demonstrated that among 385 women with GDM, 24 (6%) had β-cell–specific autoantibodies characteristic of type 1 diabetes.…”
Section: Case Narrativementioning
confidence: 99%
“…The residual β-cell mass was found to be 763 mg (methods as previously described by Campbell-Thompson et al [11]), with a pancreas weight of 82.83 g and a relative pancreas weight of 1.24 g/kg (calculated as previously described by Campbell-Thompson et al [14]). Approximately 5–10% of GDM cases may be associated with autoantibody positivity (5), and it is reasonable to suspect that the presence of autoantibodies reflects autoimmune destruction of pancreatic β-cells (2). However, direct histological evidence within the literature is lacking.…”
Section: Case Narrativementioning
confidence: 99%